Growth, Greening, and Phytochrome in Etiolated Spirodela (Lemnaceae) - Porath, Dan (1973)
Two species of Spirodela were grown aseptically in a simple mineral medium containing sucrose. Weak red light (15 erg cm(−2) sec(−1)) enhanced dark growth of S. oligorrhiza, whereas weak far red light (15 erg cm(−2) sec(−1)) when given after the red light reduced this effect. The lag period in chlorophyll accumulation (20-24 hours) could be shortened by a brief red light illumination, at both 25 C and 0 C, 12 to 24 hr before the exposure to continuous white light. The effect of red light in shortening the lag phase was diminished when high intensity of far red light (10(3)−10(4) erg cm(−2) sec(−1)) was given simultaneously with the red light. Spectrophotometric studies showed detectable amounts of phytochrome in the plants, part of which decayed immediately during a short illumination by red light. The other relatively stable, phytochrome decayed only after prolonged illumination.